Regional Banks, Financial Development, and Regional Integration in West Africa: The Case Study of Ecobank - Thuotte, Ross Daniel (Tufts Archival Research Center, 2005)
Over the past sixty years in West Africa, efforts to increase regional economic integration have been a central part of economic policy decisions. However, for many countries in the region, intra-regional trade (a key indicator of regional economic integration,) remains at a disappointingly low level. By investigating the African regional bank Ecobank, this thesis seeks to identify a new regional actor that may be able to impact regional integration in West Africa. The paper will combine literature of 'old regionalism', 'new regionalisms', and the role of the financial sector development in economic growth in order to gain a holistic perspective of how a financial institution may emulate a regional actor. This empirically-based study combines both quantitative and qualitative analyses to identify the Mechanisms by which Ecobank may affect the regionalization process. This thesis finds that the presence of Ecobank in a pair of West African countries leads to an increase in trade among the economies of that country pair over time. Another important finding is that the bank's dual mission of generating profits and fostering regional integration is integral to its capacity as a regional actor.